The relationship between the golf swing plane and ball impact characteristics using trajectory ellipse fitting - Morrison, A.; McGrath, D.; Wallace, E. S. (Journal of Sports Sciences, 2018)
The trajectory of the clubhead close to ball impact during the golf swing has previously been shown to be planar. However, the relationship between the plane orientation and the orientation characteristics of the clubhead at ball impact has yet to be defined. Fifty-two male golfers (27 high skilled, 25 intermediate skilled) hit 40 drives each in an indoor biomechanics laboratory. This study successfully fitted the trajectory of the clubhead near impact to an ellipse for each swing for players of different skill levels to help better explain this relationship. Additionally, the eccentricities of the ellipses were investigated for links to skill level. The trajectory of the clubhead was found to fit to an ellipse with RMSE of 1.2 mm. The eccentricity of the ellipse was found to be greater in the high-skilled golfers. The club path and angle of attack generated from the ellipse fitted clubhead trajectory were found to have a normalised bias-corrected RMSE of 2% and 3%, respectively. A set of "rule of thumb" values for the relationship between the club path, angle of attack and delivery plane angle was generated for use by coaches.